2018
DOI: 10.1016/j.chiabu.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported neglect, amygdala volume, and symptoms of anxiety in adolescent boys

Abstract: Experiences of psychosocial neglect affect the developing brain and may place individuals at increased risk for anxiety. The majority of research in this area has focused on children who have experienced severe psychosocial deprivation; it is not clear whether typical variation in neglect experienced in community samples would have the same neurobiological consequences as those documented in extreme samples. The present study examined the associations among self-reported childhood neglect, amygdala volume, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 76 publications
2
31
0
1
Order By: Relevance
“…In line with this, differentiated effects of abusive vs. neglectful environments on neural mechanisms linking childhood maltreatment to psychopathology and difficulties in emotional functioning have been reported recently (Dong et al, 2004;McLaughlin et al, 2014;Sheridan and McLaughlin, 2014;Humphreys and Zeanah, 2015;Zeanah and Sonuga-Barke, 2016;Roth et al, 2018). Hence, it is likely to assume that attentional biases toward threatening stimuli may be influenced differently by different forms of maltreatment.…”
Section: Introductionmentioning
confidence: 69%
“…In line with this, differentiated effects of abusive vs. neglectful environments on neural mechanisms linking childhood maltreatment to psychopathology and difficulties in emotional functioning have been reported recently (Dong et al, 2004;McLaughlin et al, 2014;Sheridan and McLaughlin, 2014;Humphreys and Zeanah, 2015;Zeanah and Sonuga-Barke, 2016;Roth et al, 2018). Hence, it is likely to assume that attentional biases toward threatening stimuli may be influenced differently by different forms of maltreatment.…”
Section: Introductionmentioning
confidence: 69%
“…Results from this analysis showed that adolescents with higher family multi‐risk index scores exhibited increased activation in the right amygdala in response to chosen gambles that were higher (relative to lower) risk during the decision phase of the task (see Figure C and Table ). The conjunction of both prior evidence implicating the right amygdala to be involved in representing family adversity in the adolescent brain (Roth, Humphreys, King, & Gotlib, ; Saxbe et al., ), and whole brain analysis identifying the right amygdala as a neural correlate of risk processing especially in adolescents from high‐risk family environments, t (133) = 4.09, p ( FWE ) < .05, led to our focus on the right amygdala in subsequent analyses. Eigenvariate values were extracted for the peak voxel coordinates of the right amygdala cortex using a 6 mm sphere (right: x = 36, y = 2, z = −23).…”
Section: Resultsmentioning
confidence: 99%
“…Previous results indicate that childhood neglect may predict deficits in the recognition of positive emotions (Young and Widom, 2014), that might explain difficulties in applying adaptive strategies, such as refocus on planning, positive reappraisal or putting a stressful life event into a more acceptable perspective. On a neurobiological level, others found that right amygdale volume mediates the association between neglect and anxiety (Roth et al, 2018) or that early exposure to either emotional or physical neglect is related to amygdala hypertrophy and mood disorders (Herzog and Schmahl, 2018). Increased risk for anxiety and mood disorders thus further reduce the capability to focus on positive outcomes in stressful live situations.…”
Section: Discussionmentioning
confidence: 99%